2009
DOI: 10.1007/s00420-009-0473-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive substances consumption in French fishermen and merchant seamen

Abstract: Alcohol and tobacco consumption are a major public health problem for seafarers. Fishermen seem to be more liable to high consumption. Working conditions may explain these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Sixteen articles studying addictions amongst seafarers were selected: 15 cross-sectional descriptive studies and 1 cohort study (Table 1) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Two studies measured urinary markers [13,14].…”
Section: Selected Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen articles studying addictions amongst seafarers were selected: 15 cross-sectional descriptive studies and 1 cohort study (Table 1) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Two studies measured urinary markers [13,14].…”
Section: Selected Articlesmentioning
confidence: 99%
“…Four articles used the criteria of hazardous drinking as defined by World Health Organisation (WHO). Prevalence varied 8.8-22% (Table 1) [19,20,24,25]. [24] showed that the prevalence of hazardous drinking was higher among fishermen than among merchant seamen: respectively 18.6% vs. 8% [24].…”
Section: Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have pointed to the high daily alcohol consumption among fishermen, as well as intensive behavioral smoking, associating the behavior and working conditions. 25,26 Another study pointed fishermen as major consumers of alcohol in the control group. In both groups, those who consumed alcohol were older, smoked more cigarettes per day, and experienced a greater frequency of accidents than those who did not consume alcohol.…”
Section: Category 2) Alcohol Consumption and Occupational Accidents: mentioning
confidence: 99%
“…In 2007, the study made by Occupational Health Department for Seamen (Service de santé des gens de mer) [18][19][20] had shown that prevalence of a positive urine test for cannabis was 14% for all seamen, without significant difference between merchant seamen (13.4%) and fishermen (13.7%). Since this study, several aspects have indicated potential increase in cannabis use and especially among fishermen making fishing trips of more than 24 h. During consultations with occupational physicians, many fishermen declared being concerned about the increasing use of cannabis.…”
Section: Introductionmentioning
confidence: 99%